Kebebasan Beragama Di Indonesia Dalam Terang Hak Asasi Manusia: Sebuah Tinjauan Filosofis - Jelvi Monica Mangundap; Ambrosius Markus Loho; Chandra Christofel Wohon (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2022)
Freedom of religion is a principle that supports individual or societal freedom to practice religion or belief in private or public space. Therefore, it is often said that religious rights and freedoms are non-derogable human rights, namely human rights which cannot be reduced under any circumstances. The problem studied in this paper is how human rights prioritize humans as subjects and describe that humans are creatures that are valued without distinction based on race, skin color, sex, gender, ethnicity, language, or any religion. Habermas, in his study of public space and religion, for example, initiated a secular society which is a transformation of views that were originally very Hegelian. With that, in the end for him, the role of religion is very much needed as a potential source for creating solidarity. The results of this paper show that when we prioritize individuals in human rights, it does not mean prioritizing the egoistic, but also including the fact that humans who have human rights are obliged to several social demands. Individual freedom always ends with respect for other individual freedoms. Humans are free if their possibilities to act, including acting in religious life, are not limited by other people. Because freedom is intrinsically lived in relationships with other people. A large country is a country inhabited by every subject who knows and is aware of freedom and responsibility in all things. A free country is a country that of course has a big responsibility to advance its country